A Case of Adrenal Metastasis in Seminoma. (21st August 2013) - Zakaria, Bouabdallah; Pierre-Etienne, Théveniaud; Véronique, Duchatelle; Vincent, Molinié; Walid, Massoud; Hervé, Baumert
Abstract : We report an uncommon case of testicular cancer with adrenal metastasis without retroperitoneal or distant metastatic disease. This situation is highly unusual. In fact, no similar case was reported in the literature. Our case is the first adrenalectomy that has been performed for secondary localization of testicular cancer. After eighteen-month followup, the patient was doing well, with no evidence of disease.